Analytical models of power losses of a three phase AC-DC rectifier for hybrid electric vehicles - Xu, Z.; You, K.; Zhang, C. (Elsevier, 2016)
This paper presents the investigation of analytical models for the approximation of conduction and switching losses of the power-switch network in a three-phase AC-DC matrix rectifier. Analytical models of conduction and switching losses can provide circuit designers with a measurable way to approximate the total losses of the given power converter at different operating points so as to estimate the trend of the loss versus the change of the operating points.